Framing Film Dokumenter Ice Cold: Murder, Coffee and Jessica Wongso Dalam Perspektif Komunikasi Pemasaran - Valentine, Aurelya; Vardiansyah, Dani (Innovative: Journal Of Social Science Research, 2024)
This research aims to identify framing in the documentary film Ice Cold: Murder, Coffee, and Jessica Wongso using Robert N. Entman's four stages of framing, including Issue Defining, Cause Diagnosis, Moral Judgement Making, and Treatment Suggestion. In this qualitative study, we apply Robert N. Entman's framing analysis technique. The research results show that Define Problems in this documentary focuses on the irregularities and injustices in this case. Diagnose Causes appears in narratives that describe irregularities in evidence and legal procedures that give rise to public confusion and doubt. Make Moral Judgment is visible when this documentary tends to be pro Jessica by highlighting the weaknesses in the court process, Treatment Recommendation Otto Hasibuan succeeded in changing the public's view of Jessica Wongso by proving that there was no cyanide in the evidence and including suggestions regarding increasing transparency and legal procedures in handling major cases like this. This research also explores how storytelling in the documentary plays a role in attracting the audience's attention in the context of marketing communications. The use of strong narrative, characterization and emotional elements helps increase audience engagement and strengthen the appeal of this film, especially in an effort to increase audience interest and engagement with the story being told.